Special concrete with polymers - Angelescu, Nicolae (2016)
The development of polymeric materials offers new perspectives of science and technology due to their outstanding properties. These properties are obtained either due to the effect of dispersion polymers and their polymerization either due to their intervention in structure formation. They were prepared epoxy resin polymer concrete, Portland cement, coarse and fine aggregate and to evaluate the influence of resin dosage on microstructures and density of such structures reinforced concrete mixtures. The paper detailing the raw materials used in experimental works and structural properties of concrete studied.